The evolution of parenteral nutrition over the past 40 years: A bibliometric overview - Özkan, Murat Bulut; Yıldırım, Murat Baki (Journal of Surgery and Medicine, 2022)
Background/Aim: Malnutrition remains a significant problem in cancer patients, intensive care patients, and patients undergoing major surgery. Although the importance of nutritional support has been proven, the preferred route for nutrient delivery is still controversial. In recent years, the use of parenteral nutrition (PN) has been increasing, and the early use of PN has become widespread once again. However, there is still no bibliometric study in the literature about PN, which has increased the number of global studies in recent years. This study aimed to analyze the scientific articles on PN published between 1980 and 2020 with statistical methods and to evaluate the subject holistically. Methods: Articles on PN published between 1980 and 2020 were analyzed using statistical and bibliometric methods. Spearman correlation coefficient was used for correlation studies. Nonlinear (cubic model) regression analysis was used to estimate the number of publications in the coming years. Keyword network visualization maps were used to identify trending topics and collaborations. Results: A total of 9424 publications were found. Of these publications, 5461 (57.9%) were articles. The top 3 contributing countries to the literature were the USA (1901, 34.8%), UK (542, 10%), and France (437, 8%). The top 3 most active institutions were Harvard University (99, 1.8%), University of Toronto (98, 1.8%), and University of California, Los Angeles (84, 1.5%). The top 3 journals with the highest number of publications were Journal of Parenteral and Enteral Nutrition (894, 16.4%), Clinical Nutrition (337, 6.2%), and Nutrition (187, 3.4%). According to the average number of citations per article, the most influential journals were Annals of Surgery (88.2, 1.5%), Gastroenterology (85.8), and Gut (81.2), respectively. Conclusion: In this comprehensive study on PN, a summary of 5461 articles were presented. The trend topics in PN research are determined and it can be said that most of them related with intensive care units and cancer patients. This article may be a valuable resource for clinicians and scientists on PN global outcomes.